Some issues of qualification of frauds committed using information systems - Kurumbayeva, A.B.; Kochshegulov, B.B. (Bulletin of the Karaganda University “Law Series”, 2022)
According to official statistics, in recent years there has been an increase in the registration of crimes of a pronounced “intellectual” nature. The objectively recorded growth of criminal encroachments on property using information technology dictates the urgent need for theoretical research and generalization of law enforcement practice. Based on the complex use of historical, comparative, and statistical methods, the authors tried to show the impact of improving substantive criminal legislation on the state of investigative and judicial practice in cases of fraud committed using information systems. The history of the regulation of liability for fraud in the criminal laws of the Soviet period that were in force on the territory of the country and the period of sovereign national legislation is traced. The rules and techniques of legal technique used in the construction of dispositions of criminal law on fraud are considered. The grounds for the criminalization of fraud committed by deception or abuse of the trust of the user of the information system are analyzed. Legal analysis and problems of qualification of this type of fraud are illustrated by materials of investigativeand judicial practice. As possible ways to improve the effectiveness of come ating fraud committed using information systems, the authors formulated proposals for changing the form of statistical reporting and conducting analytical studies on a regular basis.